OGC P38 Prognostic significance of weight loss in patients diagnosed with resectable oesophageal cancer. (7th December 2022) - Geropoulos, Georgios; Patel, Nikhil; Patel, Pranav; Doyle, Joseph; Allum, William; Chaudry, Asif; Bhogal, Ricky; Kumar, Sacheen
Abstract: Background: Weight loss is a common presenting symptom among oesophageal cancer patients. Although tumour volume-associated dysphagia can affect a patient's oral intake, other factors also contribute to weight loss. The aim of this study is to investigate and summarize the existing evidence in regards to the prognostic significance of weight loss in patients undergoing oesophagectomy. Methods: The MEDLINE (via PubMed), Cochrane Library, and SCOPUS bibliographical databases were searched by two independent reviewers. Excessive weight loss was defined as more than a 10% decrease from a patient's baseline weight. Original clinical studies, published in English, comparing long term outcomes of resectable oesophageal cancer patients with pre-treatment weight loss of >10% versus 0–10% weight loss were deemed eligible for our study. The primary endpoint of our analysis was 3-year overall survival and disease-free survival. Results: Fifteen studies with non-overlapping population reporting on 3271 (1241 reported excessive weight loss (>10%) and 1976 had 0–10% weight loss) patients, met our inclusion criteria. Early recurrence rates between the 2 groups could not be assessed as these were reported in only two of the fifteen studies. Our quantitative analysis demonstrated that patients with resectable oesophageal cancer with >10% weight loss on presentation were associated with significantly lower three-year disease-free and overall survival (OR: 0.80, 95% CI: 0.74 to 0.87, p < 0.01). Conclusions: Excessive weight loss at diagnosis is a poor prognostic factor for patients undergoing surgical treatment for resectable oesophageal cancer. It is associated with decreased disease-free and overall survival.